Gain of Chromosome 4qter and Loss of 5pter: An Unusual Case with Features of Cri du Chat Syndrome. (20th December 2012) - Sheth, Frenny; Gohel, Naresh; Liehr, Thomas; Akinde, Olakanmi; Desai, Manisha; Adeteye, Olawaleye; Sheth, Jayesh
Abstract : Here, we present a case with an unusual chromosomal rearrangement in a child with a predominant phenotype of high-pitched crying showing deletion encompassing CTNND2 due to an unbalanced translocation of chromosomes 4 and 5. This rearrangement led to a duplication of  ~ 35 Mb in 4qter which replaced 18 Mb genetic materials in 5pter. Even though, in this patient, there was no clinically obvious modification to the classical phenotypes of CdCS, and the influence of the 4q-duplication cannot be completely excluded in this case. However, the region 4q34.1–34.3 was previously reported as a region not leading to phenotypic changes if present in three copies, an observation which could possibly be supported by this case. Conclusion . This study showed that in a patient with an unbalanced translocation resulting in 5p deletion, the presence of partial trisomy of chromosome 4q could be clinically insignificant.